2019
DOI: 10.21873/invivo.11558
|View full text |Cite
|
Sign up to set email alerts
|

The Choice of Drainage Device in Complicated Glaucomas: Comparing Ahmed and Baerveldt Implants

Abstract: Background/Aim: Glaucoma is a chronic and progressive optic neuropathy which leads to deterioration of visual function. It is estimated to be the second leading cause of severe vision loss and blindness worldwide. Failure of antiglaucoma medication to sufficiently reduce intraocular pressure (IOP) and poor compliance with medication are indications for glaucoma surgery, for example using glaucoma drainage devices. Our aim was to compare the surgical outcomes following the implantation of Ahmed FP7 and Baerveld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…Our IOP results at the final postoperative examination (13.84±2.95 mmHg) were similar to those of Moschos et al, [14] but lower than those reported by Yazgan et al [7] This may have been due to the longer postoperative follow-up duration in the Yazgan et al [7] study. Although the preoperative IOP values of our cases were much higher than those of Moschos et al, [14] a satisfactory postoperative success rate (complete success in 45.2% and qualified success in 54.8% for a total of 100% surgical success) was determined. However, the success rate may decrease with longer follow-up.…”
Section: Fundingsupporting
confidence: 86%
See 3 more Smart Citations
“…Our IOP results at the final postoperative examination (13.84±2.95 mmHg) were similar to those of Moschos et al, [14] but lower than those reported by Yazgan et al [7] This may have been due to the longer postoperative follow-up duration in the Yazgan et al [7] study. Although the preoperative IOP values of our cases were much higher than those of Moschos et al, [14] a satisfactory postoperative success rate (complete success in 45.2% and qualified success in 54.8% for a total of 100% surgical success) was determined. However, the success rate may decrease with longer follow-up.…”
Section: Fundingsupporting
confidence: 86%
“…The mean follow-up duration was 32.3±20.7 months in that study of 48 refractory glaucoma cases. [7] The mean preoperative IOP level of our patients (40.84±8.27 mmHg) was much higher than that reported by Moschos et al [14] The reason may be that our study group included more complicated cases. Our IOP results at the final postoperative examination (13.84±2.95 mmHg) were similar to those of Moschos et al, [14] but lower than those reported by Yazgan et al [7] This may have been due to the longer postoperative follow-up duration in the Yazgan et al [7] study.…”
Section: Fundingmentioning
confidence: 50%
See 2 more Smart Citations
“…The IOP was postoperatively controlled using a lower number of medications in both the groups, although this number was significantly lower in patients with an Ahmed implant at the 3-year follow-up. [ 22 ] Another retrospective study performed by Tsai et al . noted a comparable result to our study, wherein during a follow-up of 12 months, the success rate (defined as 6 mmHg ≤ IOP ≤ 21 mmHg without additional glaucoma surgery or devastating complication) in the Ahmed group (48 patients) was higher than in the Baerveldt one (70 patients).…”
Section: Discussionmentioning
confidence: 99%